Die rekenarisering van die leksikografiese prosesse in die Buro van die WAT - Harteveld, P. (Lexikos, 1991)
The Computerization of the Lexicographical Processes at the Bureau of the WAT In August 1987 the Bureau of the WAT started computerizing its lexicographical processes. This article describes the advantages of computerizing, the phases of the process, the problems encountered and the results obtained. During the first phase (1987-1989) the computer was mainly used as a word processor for creating manuscript. It was not possible to transfer the dictionary text electronically to the external publishing house. The second phase (from 1990 onwards) entails the adaptation of software to editorial needs, the expansion of the computer system and the development of an electronic language database. More than three million unedited records of word material on card as well as the published volumes of the WAT will be transferred to this database. A computer field-structure for the on-screen entry of information into the dictionary and for its multipurpose extraction from the resulting text database is put forward. The direct electronic transfer of manuscript text to the Bureau’s internal reprographic department, as well as internal layout and printing are now realities. Future computer applications for expediting the editorial processes are also indicated. Keywords: computerization; lexicographical processes; Bureau of the WAT; word processing; software; hardware; electronic language database; field structure for dictionary entry and data extraction; editing on screen; text database; multipurpose data extraction; electronic transfer of manuscript; in-house publishing